Metabolic syndrome - diagnostics, pathophysiology and treatment - Weronika Wasyluk; Martyna Wasyluk; Agnieszka Zwolak; Robert Jan Łuczyk (Kazimierz Wielki University, 2019)
Abstract Metabolic syndrome, though it is not a disease included in ICD-10, is a serious epidemiological problem as much as a challenge for medicine and prevention of developed countries. The aim of this work is to discuss, based on literature, the basics of pathophysiology, diagnostic criteria and principles of treatment of the metabolic syndrome. The diagnosis of the metabolic syndrome is based on simple criteria, which include: abdominal circumference, blood pressure and triglycerides, HDL cholesterol and glucose levels. This allows the diagnosis of the metabolic syndrome at the level of primary care. The basis for treatment of the metabolic syndrome is behavioural therapy, sometimes, at non-advanced stage of the disease, it is sufficient. Due to the significant progress in pathophysiology of the metabolic syndrome, it is possible to determine its primary causes and risk factors - obesity and insulin resistance. Both of them belong to the reversible states, which is motivation to detect and treat these conditions before irreversible complications develop.